Pengaruh Stress Kerja Terhadap Kejadian Kecelakaan Kerja di Industri Kayu Lapis Bagian Rotary Jember, Indonesia - Fihris Maulidiah Suhma; Ancah Caesarina Novi; Isa Ma’rufi (Multidisciplinary Journal, 2020)
The current industrial development is getting more advanced and developing every year. The business world, including the industry, is increasingly competitive and is making the best of efforts to optimally utilize all resources, including utilizing human resources. However, efforts to optimize and utilize resources have an impact on humans or workers, namely job stress. Work stress on workers that occurs when daily data in the work environment exceeds the worker's ability to cope with or control work stress so that it will improve mental and physical workers. The general objective of this research is to analyze the effect of stress on the incidence of work accidents in one of the plywood industries in the rotary section in Jember Regency. This research is a quantitative study using an analytic observational research design with a cross sectional method. The population includes all the plywood industry workers in PT. X, Jember district, rotary part of 339 workers, with a sample size of 76 people. The sampling technique used in this study was quota random sampling with a multivariate analysis process. Based on the results of the study, it was obtained from the P value that there was no significant effect between work stress and the incidence of work accidents that occurred in the rotary section at PT. X in Jember. This is possible because the workers’ stress level is still in the medium category, and they can still cope with the stress they experience. Keyword: industry, work place accident, unsafe action, workers. Keywords: industry, work place accident, unsafe action, workers